2023
DOI: 10.3390/genes14030768
|View full text |Cite
|
Sign up to set email alerts
|

Two Complete Mitochondrial Genomes of Leptobrachium (Anura: Megophryidae: Leptobrachiinae): Characteristics, Population Divergences, and Phylogenetic Implications

Abstract: The mustache toads Leptobrachium boringii and Leptobrachium liui are two attractive species in Megophryidae, in which adult males have mustache-like keratinized nuptial spines on their upper lip. However, both are under threat due to multiple factors, of which scientific studies are still very limited. In this study, two new complete mitochondrial genomes of L. boringii and L. liui were sequenced, assembled, and annotated based on next-generation sequencing. The mitogenome lengths of L. boringii and L. liui we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…For instance, the species we previously detected in Salamandridae had a positive AT skew (Wang, Lan et al., 2022 ), whereas all the Megophryidae species in this study displayed a negative AT skew, consistent with the findings of Zhou et al. ( 2023 ). Furthermore, while the mitogenomes of species in Ranoidea exhibited gene rearrangements frequently (Igawa et al., 2008 ), no any rearrangements were identified among all the Megophryidae species examined in this study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…For instance, the species we previously detected in Salamandridae had a positive AT skew (Wang, Lan et al., 2022 ), whereas all the Megophryidae species in this study displayed a negative AT skew, consistent with the findings of Zhou et al. ( 2023 ). Furthermore, while the mitogenomes of species in Ranoidea exhibited gene rearrangements frequently (Igawa et al., 2008 ), no any rearrangements were identified among all the Megophryidae species examined in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The phylogenetic analysis revealed that Megophryidae could be divided into two well‐supported clades, supporting the classification of the two subfamilies, Megophryinae and Leptobrachiinae. The intergeneric relationships among the two subfamilies were consistent with our previous study (Zhou et al., 2023 ), with the monophyly of each examined genus also receiving support. Based on the two most recent phylogenetic studies of Boulenophrys , the genus can be further divided into three well‐supported species groups: the B. minor group, the B. omeimontis group, and the B. boettgeri group (Lyu et al., 2023 ; Qi et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations